2009
DOI: 10.1002/bdra.20639
|View full text |Cite
|
Sign up to set email alerts
|

Testing reported associations of genetic risk factors for oral clefts in a large Irish study population

Abstract: BACKGROUND Suggestive, but not conclusive, studies implicate many genetic variants in oral cleft etiology. We used a large, ethnically homogenous study population to test whether reported associations between nonsyndromic oral clefts and 12 genes (CLPTM1, CRISPLD2, FGFR2, GABRB3, GLI2, IRF6, PTCH1, RARA, RYK, SATB2, SUMO1, TGFA) could be confirmed. METHODS Thirty-one single nucleotide polymorphisms (SNPs) in exons, splice sites, and conserved non-coding regions were studied in 509 patients with cleft lip wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 53 publications
4
74
0
1
Order By: Relevance
“…However, other association studies yielded conflicting results in different populations (Carter et al, 2010;Girardi et al, 2011;Jugessur et al, 2009;Letra et al, 2010;Shi et al, 2010). It is unclear whether this association crosses ethnic barriers or whether it is anthropologic diversity.…”
Section: Introductionmentioning
confidence: 90%
“…However, other association studies yielded conflicting results in different populations (Carter et al, 2010;Girardi et al, 2011;Jugessur et al, 2009;Letra et al, 2010;Shi et al, 2010). It is unclear whether this association crosses ethnic barriers or whether it is anthropologic diversity.…”
Section: Introductionmentioning
confidence: 90%
“…The functional association has been ascribed to the fact that TGF-α is similar to Epidermal Growth Factor (EGF) and has similar effect on the cells of the bone marrow which is considered to be mitogenic and responsible for differentiation of osteoblasts. Thus, as per the work of Carter et al, it has been shown that TGF-α does not seem to have a direct role in CLP [27,28].…”
Section: Transforming Growth Factor Alpha (Tgf-α-); 2p13mentioning
confidence: 78%
“…T-box genes encode numerous transcription factors that are involved in the regulating various developmental processes and is believed to play a major role in palatogenesis [28]. Most of the studies till date reveal that a mutation in TBX 22 results in CP and ankyloglossia, though there are studies that indicate mutation of TBX 22 can result in CP alone [30].…”
Section: T-box 22 T-box Transcription Factor (Tbx22); Xq211mentioning
confidence: 99%
“…17 Analysis of two intronic SNPs (rs4673313 and rs17199393) in Irish NSCL/P showed no significant association between NSCL/P and SATB2. 18 Both TRIMM and HAPLIN methods that were used to detect multimarker effects on oral clefts of Norway and Denmark showed significant maternal effects of SATB2 gene variants for isolated cleft palate in Danish but not in Norwegian samples. 19 The expression of SATB2 during mid-facial development and palatogenesis in mouse, chick and zebrafish is highly conserved, and suggests that the SATB2 gene is under extreme evolutionary pressure.…”
Section: Discussionmentioning
confidence: 99%